Elastoplastic Analysis of Pressurized FG rotating Thick Cylinders Based on High-Order Shear Deformation Theory and Radial Return Method - Mojtaba Ghadimi; Mehdi Ghannad (Mechanics of Advanced Composite Structures)
In this paper, the elastoplastic behavior of a rotating thick cylinder is investigated. High-order shear deformation theory (HSDT) is used to define the displacement field. The cylinder is considered to be fixed at both ends and rotates around its axis with specific angular velocity. The cylinder is also made of functionally graded material (FGM), and the properties of the material are changed gradually from the inner to the outer surface. The material is supposed to be elastic-perfectly plastic and the von Mises yield criterion is used to define the state of stress. The Prandtl-Reuss flow rule is used to express the stress-strain relation in the plastic region. The radial return mapping method is applied to compute the elastoplastic stress field. The equilibrium equations and general boundary conditions of the cylinder are derived using the energy method. The elastic limit pressure and the stress analysis of the FG rotating thick cylinders have been obtained by solving the equations derived based on HSDT. The influence of the inhomogeneity constants and angular velocity of the cylinder are studied. The results are evaluated with the finite element method using Abaqus software. The main novelty of the study is investigating shear stress in the elastoplastic analysis of cylindrical shells. The results revealed that using the HSDT with the radial return mapping method has enough accuracy for the elastoplastic analysis of clamped-clamped thick cylindrical structures.